(untitled) (The Journal of Modern Project Management, 2022)
There are projects for which the classical Critical Path method (CPM) or Precedence Diagramming Method (PDM) scheduling techniques are not the most suitable. Several alternative approaches have been developed over the last two decades to cope with the scheduling requirements of construction projects that are made of either repetitive activities or activities that have a linear development. Construction projects, and more specifically large-scale construction endeavors, are often composed of a mixture of repetitive activities, linear activities and more conventional project activities. The approach that is proposed in the present article enables construction practitioners to consider these three types of activities in a unique scheduling model — called Unified Project Scheduling System (UPSS) — that has a level of complexity similar to the one of CPM or PDM. UPSS has been designed so that most of the resource-constrained project scheduling algorithms can be used.